التدريب وعلاقته في التخفيف من حوادث العمل في مؤسسة الغاز والكهرباء - بلوزي, امال; بوليفة, هبة الرحمان (University of Eloued جامعة الوادي, 2021)
ملخص الدراسة: هدفت هذه الدراسة إلى التعرف على مدى مساهمة التدريب أثناء الخدمة في تخفيف حوادث العمل وهذا من خلال تساؤل التالي :هل يساهم التدريب أثناء الخدمة في تخفيف حوادث العمل ؟في مؤسسة سونلغاز والكهرباء بجامعة. فقد حاولت دراستنا الإجابة على الفرضيات التالية: _يرتبط تخفيف حوادث العمل بمدى استخدام العمال للسلوكيات والأساليب الوقائية. _تساهم البرامج التدريبية في تنمية المهارات والقدرات المساعدة على تحسين أداء العمل. ولتحقق من أهداف الدراسة اعتمدنا على أداة من أدوات جمع البيانات والمتمثلة في الاستبيان الذي احتوى على ثلاث محاور :المحور الأول البيانات الشخصية ،المحور الثاني حول التدريب و،المحور الثالث حول حوادث العمل ويتضمن كل من المحورين على (15)سؤالا ،فقد اتبعنا في دراسة المنهج الوصفي وهذا لتناسبه مع متطلبات الدراسة،كما احتوت الدراسة على (50)عينة من عمال وعاملات مهنيين وكان اختيارها بطريقة عشوائية وخلصت نتائج الدراسة إلى : _يساهم التدريب في تطوير أساليب العمل التقليدية والاتجاه نحو الجودة في العمل. _أن عملية التدريب العاملين ساهمت في تخفيف حوادث العمل . _أن المؤسسة تعمل على ووضع أهداف تدريبية تجعل العامل يعمل بأكثر كفاءة. Abstract: This study aimed to identify the extent to which in-service training contributes to mitigating work accidents, through the following question: Does in-service training contribute to mitigating work accidents? Our study attempted to answer the following hypotheses: The reduction of work accidents is related to the extent to which workers use preventive behaviors and methods. Training programs contribute to developing skills and capabilities that help improve work performance. In order to achieve the objectives of the study, we relied on one of the data collection tools represented in the questionnaire, which contained three axes: the first axis is personal data, the second axis is about training and, the third axis is about work accidents, and each of the two axes contains (15) questions. The descriptive approach and this is to suit the requirements of the study. The study also included (50) samples of professional male and female workers, and they were chosen randomly. The results of the study concluded that: Training contributes to the development of traditional work methods and the trend towards quality at work. The process of training employees contributed to reducing work accidents. _The institution is working on and setting training objectives that make the worker work more efficiently
دائرة جامعة – ولاية المغير -
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: التدريب، حوادث العمل; Formation, accidents du travail; Training, work accidents